Oral antiseptics in the reduction of viral load of SARS-COV-2 in dental consultation - Guerra Robalino, Shirley (2021)
The increase in COVID-19 infections worldwide and the susceptibility of the dental professionals due to close contact with patients' saliva and the production of aerosols carrying SARS-CoV-2, has generated the search for new preventive measures with the intention of reducing the risk present in the dental office. Recent research, based on the antiviral activity of some oral antiseptics, such as: chlorhexidine, povidone iodide, cetylpyridinium chloride and hydrogen peroxide; have focused on evaluating the efficacy that these different solutions might have against the new virus in media similar to the oral cavity. Based on this, this article has the objective of conducting a review on the antiviral efficacy of mouth rinses on SARS-CoV-2 as a preventive measure against the risk of transmission in the dental office. A search was made for original articles relevant to the topic, the databases were Medline and Scopus; electronic libraries: SciELO, WILEY, and academic search engines such as Google Scholar. In terms of results, iodopovidone has been shown to be more effective against COVID-19 followed by hydrogen peroxide, cetylpyridinium chloride and chlorhexidine. While clinical studies regarding the duration of efficacy in the oral cavity are limited, it was concluded that mouthwashes appear to be a good preventive, safe and a complementary option in dental practice; while awaiting more effective therapies or a vaccine.